EXPLORING THE RELATIONSHIP BETWEEN SOCIAL MEDIA USE AND MENTAL HEALTH IN ADOLESCENTS: A LONGITUDINAL STUDY - Sanjay Bamnawat, Sandeep kumar Bamnawat (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This project is a longitudinal investigation into the relationship between the usage of social media and mental health in adolescents. The purpose of this study is to gain an understanding of how different patterns of involvement with social media influence psychological well-being over the course of time. As a result of the widespread incorporation of social media into everyday life, adolescents are increasingly exposed to the advantages as well as the possible dangers that come along with it. This study takes a thorough approach by following a group of adolescents over the course of several years in order to evaluate the ways in which their use of social media has changed and the mental health outcomes that have resulted from those changes.The data was acquired using surveys and psychological evaluations that measured social media habits, such as the amount of time spent online, the types of platforms utilised, and the patterns of interaction. Additionally, mental health indicators such as anxiety, depression, and self-esteem were among the factors that were taken into consideration. Additionally, moderating factors such as social support, offline social interactions, and individual differences are taken into consideration while conducting this study.